Inscriptions found from the old group of temples at Chandrabhaga - Temples of India Project Team (Jio Institute, 2024)
Inscriptions are found from the old group of temples at Chandrabhaga on the pillar of the Sitaleshwar Temple (right) and from the Navadurga or Kalika Devi Temple (left).